A Collective Biography: Women Pioneers of Physical Education at Anstey Physical Training College, United Kingdom. Issue 16 (2nd November 2017) - Benn, Tansin
Abstract: The aim of the historical analyses of the contributions of three women principals of a teacher training institution in England was to increase understanding of women as agents of change. Located in different historical, social, political, and economic eras the three women were pioneers and leaders responsible for shaping the profession of teaching physical education in different ways. Themes that emerged from document analyses, using figurational or process theory, resulted in the framework of professionalization, academicization and internationalization that is used to structure the paper. Ways in which the three women principals, Rhoda Anstey, Marion Squire, and Muriel Webster, contributed in each of the three processes of change within the profession are highlighted. All the women were principals of Anstey College of Physical Training, Birmingham, England, which opened in 1897 and was closed in 1984. The analyses illustrates long-term processes of change influenced by many aspects such as: the bifurcation of training for careers in medicine and education; increasing specialization; increasingly sophisticated systems of accreditation; political intervention to control and centralize education and its training institutions; and the drive for economic efficiencies as small institutions experienced forced mergers with larger institutions where power differentials were such that closure was inevitable.